The Dynamics of Conflict in the Relocation of Traditional Market Vendors in Gambut Subdistrict Banjar Regency - Muhammad Hassel Yasa Satria; Rochgiyanti Rochgiyanti; Sriwati Sriwati (JURNAL PENDIDIKAN IPS, 2025)
This research discusses the conflict dynamics of the relocation of Kindai Limpuar Market traders in Gambut Sub-district, Banjar Regency, South Kalimantan. The Banjar Regency Government built the New Gambut People's Market as an effort to organize the market and reduce traffic congestion due to trading activities on the road shoulder. However, the plan to relocate traders from Kindai Limpuar Market faced resistance due to the strategic location of the old market, the convenience of trading, the cost of renting stalls, and the lack of supporting facilities in the new market. This research uses a descriptive qualitative method with a phenomenological approach to describe the subjective experiences of traders, consumers, and the surrounding community towards the relocation conflict. The technique of determining informants was carried out through snowball sampling, so that 15 traders and 5 consumers were obtained. Data collection techniques were conducted through in-depth interviews, field observations, and documentation. The results showed that the conflict was vertical between traders and the local government, triggered by differences in interests and unpreparedness of infrastructure. As a result, the Gambut Baru People's Market was abandoned and the building was used as a cattle market and garbage dump. This research recommends a participatory approach in planning market relocation and infrastructure improvements as an effort to reduce conflict and maximize the utilization of market facilities.